Clinical profile and mortality of Sars-Cov-2 infection in cancer patients across two pandemic time periods (Feb 2020–Sep 2020; Sep 2020–May 2021) in the Veneto Oncology Network: The ROVID study. (May 2022) - Dieci, Maria V.; Azzarello, Giuseppe; Zagonel, Vittorina; Bassan, Franco; Gori, Stefania; Aprile, Giuseppe; Chiarion-Sileni, Vanna; Lonardi, Sara; Oliani, Cristina; Zaninelli, Marta; Chiari, Rita; Favaretto, Adolfo; et al.
Abstract: Introduction: We analyzed a cohort of patients with cancer and Sars-Cov-2 infection from the Veneto Oncology Network registry across two pandemic time periods. Materials and methods: 761 patients with cancer and SARS-CoV-2 infection were included. Results: 198 patients were diagnosed during the first pandemic time period (TP1; February 2020 September 2020), 494 during TP2 before the vaccination campaign (TP2/pre-vaccination; September 2020-21 February 2021) and 69 in TP2/post-vaccination (22 February 2021-15 May 2021). TP2 vs TP1 patients were younger (p = 0.004), showed more frequently a good performance status (p < 0.001) and <2 comorbidities (p = 0.002), were more likely to be on active anticancer therapy (p = 0.006). Significantly fewer patients in TP2 (3-4%) vs TP1 (22%) had an in-hospital potential source of infection (p < 0.001). TP2 patients were more frequently asymptomatic (p = 0.003). Significantly fewer patients from TP2 were hospitalized (p < 0.001) or admitted to intensive care unit (p = 0.006). All-cause mortality decreased from 30.3% in TP1, to 8.9% and 8.7% in the two TP2 periods (p < 0.001), reflected by a significant reduction in Sars-Cov-2-related mortality (15.2%, 7.5% and 5.8% in the three consecutive time periods, p = 0.004). Conclusions: Differences in clinical characteristics and features of Sars-Cov-2 infection between TP1 and TP2 reflect the effects of protective measures and increased testing capacity. The lower mortality in TP2 is in line with a less frail population. However, the vast majority of death events in TP2 were related to COVID-19, reinforcing the priority to protect cancer patients. Highlights: COVID-19-related mortality in cancer patients decreased over time. Pts from the second time period were younger and in better clinical conditions. In-hospital contagion was significantly reduced in the second pandemic time period. Protecting cancer patients from Sars-Cov-2 infection is a priority.